Distinct adverse outcomes and lipid profiles of erythrocytes upon single and combined exposure to cadmium and microplastics. (November 2022) - Wang, Lixin; Xu, Man; Chen, Jiamin; Zhang, Xuan; Wang, Quanshu; Wang, Yingxue; Cui, Jiansheng; Zhang, Shuping
Abstract: The growing accumulation of environmental microplastics (MPs) has become a global concern. MPs are capable to interact with other environmental contaminants leading to altered toxicity. Red blood cells (RBCs), are the target with highest priority for most of toxic xenobiotics after entering blood stream. Whether co-existence of MPs changes the toxicity of cadmium, a typical hemolysis inducer, in RBCs is unknown. We investigated the adverse effects of CdCl2 and Polystyrene-MPs (PS-MPs) on RBCs in mice. We found that CdCl2 induced mild microcytic hypochromic anemia while PS-MPs induced polycythemia vera, indicating distinct outcomes between them. Moreover, co-treatment of PS-MPs with CdCl2 did not change the phenotype of microcytic hypochromic anemia, indicating an antagonistic relationship between CdCl2 and PS-MPs. However, the lipid profiles were also distinct between single exposure and combined exposure to CdCl2 and PS-MPs. The significant changed lipids were mainly involved in altering the physiochemical or biological properties of RBCs, including decreased membrane components, disrupted bilayer thickness and intrinsic lipid curvature. These results indicated impaired membrane functions of RBCs. The altered lipid profiles observed in the current study may represent new and previously unrecognized harmful characteristics of cadmium and MPs on erythrocytes at low dose without apparent induction of anemia. Graphical abstract: Image 1 Highlights: CdCl2 and Polystyrene-Microplastics (PS-MPs) induced distinct effects on erythrocyte. CdCl2 and/or PS-MPs increased intracellular Ca 2+ level and altered lipid profiles. Membrane components, bilayer thickness and membrane curvature were altered.